2000
DOI: 10.1046/j.1469-8137.2000.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

The daily integral of growth by Planktothrix rubescens calculated from growth rate in culture and irradiance in Lake Zürich

Abstract: In Lake Zu$ rich, populations of the cyanobacterium Planktothrix rubescens develop in the metalimnion during the summer and become gradually entrained in the deepening surface mixed layer during the autumn. It had previously been demonstrated that the daily integrals of photosynthetic production accounted for the growth observed in the metalimnion and greatly exceeded the smaller increase during the autumn. We have now determined the relationship between growth rate (µ) and irradiance (I ) in cultures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(119 citation statements)
references
References 35 publications
8
111
0
Order By: Relevance
“…The highest differences of growth rate (m max ) between P. agardhii and C. raciborski in monocultures, concerned the low light intensity (P < 0.01) and starvation and/or low nutrient concentration (P< 0.001). With regard to light intensity, P. agardhii had a higher m max (0.65 d x1 ) at low light than at 75 mmol photons m x2 .s x1 , which corroborated previous studies (Davis and Walsby, 2002;Oberhaus et al, 2007), and highlighted the high affinity of this species for low irradiance (Mur and Beydorff, 1978;Bright and Walsby, 2000). Consequently, P. agardhii grew faster and outcompeted C. raciborskii with regard to biomass (IVF and biovolumes), especially at day 6 in our study, which are consistent with Bonilla et al (2012) findings, who reported that P. agardhii had a higher capacity for growth than C. raciborskii under low light intensity.…”
Section: Discussionsupporting
confidence: 89%
“…The highest differences of growth rate (m max ) between P. agardhii and C. raciborski in monocultures, concerned the low light intensity (P < 0.01) and starvation and/or low nutrient concentration (P< 0.001). With regard to light intensity, P. agardhii had a higher m max (0.65 d x1 ) at low light than at 75 mmol photons m x2 .s x1 , which corroborated previous studies (Davis and Walsby, 2002;Oberhaus et al, 2007), and highlighted the high affinity of this species for low irradiance (Mur and Beydorff, 1978;Bright and Walsby, 2000). Consequently, P. agardhii grew faster and outcompeted C. raciborskii with regard to biomass (IVF and biovolumes), especially at day 6 in our study, which are consistent with Bonilla et al (2012) findings, who reported that P. agardhii had a higher capacity for growth than C. raciborskii under low light intensity.…”
Section: Discussionsupporting
confidence: 89%
“…Average surface concentrations of DIP and TP can considered to be very good (r>0.85, Fig.8). The measured DIP concentrations during summer tend to be somewhat higher than the simulations, which might be, to some extent, due to the river uxes that not by internal waves or upwelling events that occur frequently in Lake Bourget (Cuypers et al, 2011), given their low growth rates (Bright and Walsby, 2000) and limited losses imposed by zooplankton (Kurmayer and Jüttner, 1999). On the other hand, their growth at 10-20 m depth (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…P. rubescens was assigned as a separate algal group because of its distinctive eco-physiology characterized by low-light tolerance (Walsby and Schanz, 2002), slow growth (Bright and Walsby, 2000), and grazing defense (Kurmayer and Jüttner, 1999) as well as the fact that it represented about half of the phytoplankton assemblage in some years ( Fig. 1,3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations